Spectrum of cutaneous manifestations in lupus erythematous -a dermatologist perspective - Bhattarai, S; Agrawal, S; Rijal, A; Sharma, SK; Dhakal, SS (Health Renaissance, 2012)
Background: The cutaneous manifestations of lupus erythematosus (LE) specific skin disease consists of acute cutaneous LE (ACLE), Subacute cutaneous (SCLE) and Chronic cutaneous (CCLE). Objective: To evaluate the spectrum of cutaneous manifestation in patients of LE. Methods: A case series of 41 clinically diagnosed cases of LE attending the outpatient department of Dermatology, BPKIHS were evaluated for the specific and non-specific skin changes. Results: All the patients enrolled in the study were female,with the age ranging from 14-64 years. ACLE was detected in 22/41(78.04%). Malar rash was the frequent skin lesion. CCLE was seen in 6/41 (14.63%) patients with classical discoid lesions (localized and generalized) in 4/6(66.66%) and 2/6(33.33%) respectively. Non specific skin lesions were found in 30/ 41(73.17%) of patients. Mucosal ulcers were seen in 23/41(56.09%), Facial telangiectasias 20/41(48.78%), Raynaunds phenomena 22/41(53.65%), Chronic urticaria 9/41(21.95%), Nail changes 12/41(29.26%) and non scarring alopecia was seen in 6/41(14.63%) patients. Eye involvement was seen in 3/41(7.3%), cutaneous vasculitis in 5/41(12.19%) and scaring alopecia in 3/41(7.3%) patients. Conclusion: The cutaneous manifestations of patients with lupus erythematosus (LE) are very frequent, show a great variety and can occur at any stage of the disease. DOI: http://dx.doi.org/10.3126/hren.v10i1.5999 HREN 2012; 10(1): 8-11